Impact of ocean acidification on microzooplankton grazing dynamics - Shi, Wenting; Fu, Xiaoting; Han, Yabo; Qin, Jiahui; Sun, Jun (Frontiers in Marine Science, 2024)
This study focuses on the potential impacts of atmospheric carbon dioxide (pCO2) levels projected to reach 800 ppm by the end of the century, particularly through ocean acidification, on marine ecosystems. Concentrating on the coastal areas of Bohai, this research investigates how acidification affects the grazing patterns of microzooplankton. Employing dilution techniques and Eco physiological methods, we explored not only grazing behaviors but also the dynamic interactions between microzooplankton and phytoplankton communities, along with variations in the activity of superoxide dismutase. Our findings indicate that under acidic conditions, there is a shift in the phytoplankton community structure with changes in dominant species. The grazing rate of microzooplankton significantly decreases, while the growth rate of phytoplankton increases. Moreover, short-term acid exposure leads to an increase in microzooplankton superoxide dismutase activity, suggesting an adaptive response to mitigate oxidative stress. These results underscore the need for further research into the long-term effects of ocean acidification on microzooplankton and their role in marine secondary productivity.